Influence of biomass raw materials on the flaming combustion behavior of highly densified biomass briquette - Hiroyuki ITO; Ryo TOKUNAGA; Shumpei NOGAMI; Masayoshi MIURA (Nihon Kikai Gakkai ronbunshu, 2019)
On the flaming combustion of highly densified cypress cylindrical briquette of which diameter/length ratio is 1/2 in the high temperature air, it was reported that the flaming combustion duration is proportional to the product of the inverse square of the specific surface area and the briquette density. However, the influence of biomass raw material on the combustion behavior is not clarified yet. To utilize various biomass as raw material of briquette fuel, the knowledge on this should be obtained. The objective of the present study is to confirm the influence of biomass raw material on the flaming combustion behavior, especially, the flaming combustion duration. Cypress, bamboo, rice husk and paper are used as raw material of the briquette. From the results of the thermogravimetric analysis and the estimation of lignin content in the biomass samples, it was observed that the activation energy decreases with increasing the lignin content. From the results of combustion experiments, it was found that the flaming combustion durations for each biomass raw material are proportional to the product of the inverse square of the specific surface area and the briquette density. It is suggested that these proportional constants have the correlation with the mass percentage of the cellulose in the biomass.